Desarrollo de aplicación móvil para la gestión de domicilios en la lechonería don chancho (2021)
In the dairy industry on Calle 27 sur in the city of Bogotá, due to the small size of commercial premises, it is not possible to have a computer, which allows keep a systematic control of orders; what has generated different problems such as: forgetting orders, human errors in home management, loss of checkbooks, purchase of excess raw material, non-compliance with the delivery time, etc .; Due to the aforementioned problem, the owner of the Lechonería Don Chancho wants the development of a mobile application for taking orders and managing addresses